Clinical outcomes of COVID-19 caused by the Alpha variant compared with one by wild type in Kobe, Japan. A multi-center nested case-control study. Issue 3 (March 2023) - Doi, Asako; Iwata, Kentaro; Nakamura, Tadahiro; Oh, Koji; Isome, Kenichi; Hasegawa, Kohei; Kuroda, Hirokazu; Hasuike, Toshikazu; Seo, Ryutaro; Kosai, Hisato; Nakanishi, Noriko; Nomoto, Ryohei; et al.
Abstract: Objectives: The emergence of the Alpha variant of novel coronavirus 2019 (SARS-CoV-2) is a concerning issue but their clinical implications have not been investigated fully. Methods: We conducted a nested case-control study to compare severity and mortality caused by the Alpha variant (B.1.1.7) with the one caused by the wild type as a control from December 2020 to March 2021, using whole-genome sequencing. 28-day mortality and other clinically important outcomes were evaluated. Results: Infections caused by the Alpha variant were associated with an increase in the use of oxygen (43.4% vs 26.3%. p = 0.017), high flow nasal cannula (21.2% vs 4.0%, p = 0.0007), mechanical ventilation (16.2% vs 6.1%, p = 0.049), ICU care (30.3% vs 14.1%, p = 0.01) and the length of hospital stay (17 vs 10 days, p = 0.031). More patients with the Alpha variant received medications such as dexamethasone. However, the duration of each modality did not differ between the 2 groups. Likewise, there was no difference in 28-day mortality between the 2 groups (12% vs 8%, p = 0.48), even after multiple sensitivity analyses, including propensity score analysis. Conclusion: The Alpha variant was associated with a severe form of COVID-19, compared with the non-Alpha wild type, but might not be associated with higher mortality.